2021
DOI: 10.32920/ryerson.14656038.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UHPC Infilled Circular steel Tube Column Design

Abstract: Previous researchers studied the behavior of Ultra-High Performance Concrete (UHPC) columns confined with steel tubes. However, predicting the influence of the confinement effect and the compressive capacity of these columns has yet to be further examined. Currently, the Canadian design code limits for reinforced concrete do not reach the strength nor the strain produced by using UHPC. This project uses the Canadian design methods for a cross-section of UHPC to form a column interaction curve and compared it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Deng et al [34] conducted a drop hammer impact test on simply supported circular CFST, circular post-tensioned concrete-filled steel tube and circular steel fibre reinforced concrete-filled steel tube specimens with the compressive strength of concrete less than 60MPa. It was found that both types of these specimens demonstrate superior impact resistance than the regular concrete CFST specimens, and using the pre-stressed strands and steel fibres can effectively restrain the cracks in the tension area of the core concrete.…”
Section: Steel Tube Filled With Uhpcmentioning
confidence: 99%
“…Deng et al [34] conducted a drop hammer impact test on simply supported circular CFST, circular post-tensioned concrete-filled steel tube and circular steel fibre reinforced concrete-filled steel tube specimens with the compressive strength of concrete less than 60MPa. It was found that both types of these specimens demonstrate superior impact resistance than the regular concrete CFST specimens, and using the pre-stressed strands and steel fibres can effectively restrain the cracks in the tension area of the core concrete.…”
Section: Steel Tube Filled With Uhpcmentioning
confidence: 99%